PENGARUH KEBIJAKAN ALOKASI ASET DAN TINGKAT RISIKO TERHADAP KINERJA REKSA DANA DI INDONESIA (PERIODE 2016-2018) - Yudhistira, Ahmad Hanif Dinsri; Putra, R. Aditya Kristamtomo (Politeknik Negeri Ambon, 2020)
This study aims to determine, explain and analyze the effect of asset allocation policies and risk levels on the performance of Islamic mutual funds in Indonesia (Period 2016-2018). The independent variable in this study is the Asset Allocation Policy and Risk Level, while the dependent variable in this study is the Performance of Sharia Mutual Funds. The sample selection technique used purposive sampling and used 10 samples of Islamic mutual funds. The method used to calculate the performance of Islamic mutual funds is the Sharpe Ratio. The method used is quantitative methods with descriptive approach to the verification by descriptive statistical tests, classic assumption, multiple linear regression analysis, coefficient of determination, and hypothesis testing using Software SPSS 16. The results show that asset allocation policy variables and the level of risk has a positive and significant impact on the performance of Islamic mutual funds registered with the OJK and still active in the 2016-2018 period. The coefficient of determination test results show that the value of Adjusted R Square is 0.461. The results of 46.1% state that the independent variable can explain the dependent variable, while the remaining 53.9% is explained by other factors not examined in this study.